The Role Of Service Quality In Measuring Customer Behavioral Intention In Using BSI Mobile Banking - Teguh Iman Basuki; Dodi Supriyanto; Yunia Mulyani Azis (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Currently, mobile banking technology has been widely used by banks to provide convenience to customers in carrying out financial transactions. The use of information technology by banks shows that banks can provide the best service. With the number of BSI customers amounting to 19.65 million, it would be impossible if BSI did not utilize information technology to implement good banking governance. However, BSI Mobile, used by customers, still often experiences problems so customers do not feel calm and safe when using mobile banking. This research aims to determine customer perceptions when using BSI Mobile in every transaction. The research results show that two constructs do not have a significant effect, namely the speed and security variables so user expectations regarding high-security factors and adequate speed cannot be met by BSI mobile banking, so these two variables have not met user satisfaction. In contrast, the other two variables have a significant influence, namely the accuracy and trust variables on behavioral intention. The accuracy and trust variables can meet user expectations that BSI mobile banking can provide accurate and highly trustworthy information so that users plan to use BSI mobile banking in their financial transactions in the future or even users always use BSI mobile banking in all their financial transactions.